Analysis of a Multistage Solar Thermal Energy Accumulator - Reyes-Salinas, A; Sepulveda-Palma, F; Henriquez-Vargas, L; Vasquez-Fajardo, J; Pailahueque-Barahona, N (Elsevier Ltd, 2019)
The present work evaluates the effect of using two paraffin wax with different solidification points as PCM, stored in soda cans and sequentially distributed, on the discharge efficiency of solar thermal energy accumulators in laboratory and prototype scales. The discharge efficiency ranges found were [74%,92%] and [49%,61%] for the laboratory and prototype scale models respectively. Greater efficiency values were obtained in both accumulators when the first rows of soda cans exposed to the incoming air was filled with the PCM of lower solidification point (41 °C) and the last row with PCM of higher solidification point (56 °C). Numerical solution of the mathematical modeling allowed to predict the outlet air temperature which compared with experimental data. Bigger discrepancies with the simulation results were obtained in the prototype scale accumulator due to the variability of the environmental conditions. As conclusion we stated that it is possible to enhance the discharge efficiency of a solar energy accumulator by using two PCM with different solidification points. The implemented mathematical model allowed to predict the time evolution of the air temperature at the accumulators outlet. Row order and paraffin wax type allow to adjust the energy discharge rate depending on the application type. © 2019 Elsevier Ltd